Searching for ultra-fast outflows in AGN using variability spectra. Issue 1 (28th January 2020) - Igo, Z; Parker, M L; Matzeu, G A; Alston, W; Alvarez Crespo, N; Fürst, F; Buisson, D J K; Lobban, A; Joyce, A M; Mallick, L; Schartel, N; Santos-Lleó, M
ABSTRACT: We present a qualitative search for ultra-fast outflows (UFOs) in excess variance spectra of radio-quiet active galactic nuclei (AGNs). We analyse 42 sources from the spectroscopic UFO detection sample, and an additional 22 different sources from the variability sample. A total of 58 sources have sufficient observational data from XMM–Newton EPIC-pn and variability for an excess variance spectrum to be calculated. We examine these spectra for peaks corresponding to variable blue-shifted H- and He-like ion absorption lines from UFOs. We find good evidence for such outflows in 28 per cent of the AGN sample and weak evidence in a further 31 per cent, meaning that ∼30–60 per cent of the AGN sample hosts such UFOs. The mean and median blue-shifted velocity is found to be ∼0.14c and 0.12c, respectively. Current variability methods allow for a fast, model-independent determination of UFOs; however, further work needs to be undertaken to better characterize the statistical significance of the peaks in these spectra by more rigorous modelling. Detecting good evidence for variable UFO lines in a large number of sources also lays the groundwork for detailed analysis of the variability time-scales of the absorbers. This will allow us to probe their densities and hence distances from the central supermassive black hole.